PENGARUH INTENSITAS MODAL, GROWTH OPPORTUNITY DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BEI TAHUN 2020-2022 - MIA WIDYA SARI; IRA GUSTINA; YUSRIWARTI YUSRIWARTI; SURYANI SURYANI (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This research investigates the impact of capital intensity, growth opportunities, and institutional ownership on accounting conservatism within the property and real estate sector listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. By employing a purposive sampling approach, a total of 45 companies were identified as the study’s sample from the broader population. The analysis relies on secondary data sourced from official financial and annual reports available on the IDX website (www.idx.co.id) during the observation period. Utilizing multiple linear regression as the analytical tool, the findings from the partial t-test reveal that while capital intensity and institutional ownership significantly influence accounting conservatism, growth opportunities do not show a measurable effect. Furthermore, the simultaneous f-test confirms that capital intensity, growth opportunities, and institutional ownership collectively exert a significant influence on accounting conservatism practices in the sampled firms.